2017
DOI: 10.1176/appi.focus.20170005
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder in Primary Care: Integrated Care Experiences

Abstract: Primary care clinics are increasingly implementing collaborative care models to care for patients with psychiatric illnesses in primary care. The evidence base for the effectiveness of collaborative care has largely been derived from the care of patients with depression or anxiety disorders, although psychiatrists working in primary care may encounter patients with illnesses other than depression or anxiety disorder, notably bipolar disorder. Patients with bipolar disorder report having received treatment in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Of practical importance, the CMFC is widely eligible for insurance re-imbursement for PCPs. The CMFC assesses six common mental disorders (Beck et al, 2019 ; Cerimele & Kern, 2017 ; Wittchen et al, 2003 ) frequently found in primary care settings: (a) Major Depressive Disorders (MDD), (b) Anxiety Disorders with a primary focus on Generalized Anxiety Disorder (GAD), (c) Bipolar Disorders, (d) Attention-Deficit/Hyperactivity Disorders (ADHD), (e) Somatic Symptom Disorders, and (f) Substance and Alcohol Use Disorders.…”
Section: A Two-tiered Electronic Approach To Mental Health Screeningmentioning
confidence: 99%
“…Of practical importance, the CMFC is widely eligible for insurance re-imbursement for PCPs. The CMFC assesses six common mental disorders (Beck et al, 2019 ; Cerimele & Kern, 2017 ; Wittchen et al, 2003 ) frequently found in primary care settings: (a) Major Depressive Disorders (MDD), (b) Anxiety Disorders with a primary focus on Generalized Anxiety Disorder (GAD), (c) Bipolar Disorders, (d) Attention-Deficit/Hyperactivity Disorders (ADHD), (e) Somatic Symptom Disorders, and (f) Substance and Alcohol Use Disorders.…”
Section: A Two-tiered Electronic Approach To Mental Health Screeningmentioning
confidence: 99%